The Analysis of Primary School Student Knowledge and Participation towards Traditional Games - Gustiana Mega Anggita; Mohammad Arif Ali; Sugiarto Sugiarto; Siti Baitul Mukarromah (JUARA : Jurnal Olahraga, 2020)
This study aims to analysis elementary students’ understanding and participation in traditional game. This is a descrivtive research using survey method. Sample in this study was upper class students of MI Nurul Yaqien. The research instrument used was a questionnaire. Data analysis technique used is percentage or procentage correction. The results showed that 94.44% of students know traditional games. 71.43% of students understand traditional games. 91.67% of students are involved in traditional games. Conclusion of this research is the knowledge and participation of MI Nurul Yaqien students in traditional games is excellent. While their understanding of traditional games is in the sufficient category.